La lecto-escritura en los estudiantes kichwa hablantes del subnivel de educación básica media periodo 2016-2017 - Guato Guaisapanta, Enith Susana (2017)
The diversity that is in today’s society should be considered in the educational field as an axis in which the pedagogical process generates integration and inclusion spaces with the aim of achieving the sustainable life way achievent and development for all people within multicultural societies by the dialogue creation, respect, and understanding between different cultural groups. This research project provides diagnoses that contribute to future research related to reading-writing in Kichwa-speaking students, due ti the fundamental role in academic development. This research work was born from problems presented by students in all study areas mainly in the Language and Literature area, “Leopoldo N.Chávez” Elementary School about literacy reading and writing its influence on the teaching process-learning, which can be evidence of difficulty and confusion of words, because the students are Kichwa speakers and are prepared in a Hispanic institution, parents are unaware of how to help their children who are not prepared their Spanish language, teachers do not handle the Kichwa language, affecting the normal development of the teaching-learning process. The objective of this research is focused on determining the incidence of reading and writing in the teaching-learning process in the students of Kichwa in the level of basic education of the U. Educ. "Leopoldo N.Chávez", as well as to contribute with possible methodological strategies that allow an adequate development of the teaching-learning process with the purpose of imparting in the students the knowledge that allows them to have fluency at the time of making a reading that is understandable and therefore improve their writing, apply an investigation of field and exploration, with a mixed approach, that is, taking into account the qualitative and quantitative, as well as using the inductive-deductive, statistical methods, which helped to analyze in greater depth the difficulty that children have in learning of a second language, different from the mother tongue. A fundamental aspect is the methodological strategies that allow an adequate development of the teaching-learning process to improve student learning. Kichwa speakers have no discrimination and are able to improve languages for their development in society.